(3JQGLe eTGjN (B" (3TjNJfG (B" (3SGQg HfJ GdYR Hf LeGYIs - (3SQGL GdOjf eMeO GdeYOh YeQ Hf Jbi GdOjf Hf agO GdgGTei Gdecjs; (3GHf agO , YeQ Hf eMeO Hf eMeO Hf CHj GdNjQ eMeO Hf eMeO Hf YHO Gddg Hf agO GdbQTj GdgGTej, CHj GdNjQ , fLe GdOjf,J (B885 (3g` s ((3GdceGd CHj TQjQa s)
(3ChdgG (B:s
(3GdMeO ddg hGdUdGg hGdSdGe Ydi QShd Gddg , hbaJ Ydi JQLeI deTGjN TSNJfG SGQg s
(3BNQgG (B:s
(3gPG BNQ eG GfJbjJg ef eTjNI SGQg HfJ GdYR Hf LeGeI hMPaJ CSeGA de CLO ef PcQgG cHjQ bGFOg s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3LeYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B63 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B318s
Keywords: (3GdJGQjNs